On the relation of Carleson’s embedding and the maximal theorem in the context of Banach space geometry - Hytönen, Tuomas; Kemppainen, Mikko (MATHEMATICA SCANDINAVICA, 2011)
Hytönen, McIntosh and Portal (J. Funct. Anal., 2008) proved two vector-valued generalizations of the classical Carleson embedding theorem, both of them requiring the boundedness of a new vector-valued maximal operator, and the other one also the type p property of the underlying Banach space as an assumption. We show that these conditions are also necessary for the respective embedding theorems, thereby obtaining new equivalences between analytic and geometric properties of Banach spaces.